Engaging Local Private Operators in Water Supply and Sanitation Services - Triche, Thelma; Requeno, Sixto; Kariuki, Mukami (World Bank, Washington, DC, 2012)
Programs to reform urban utilities and to engage the private sector have tended to focus on large cities and on transactions with large foreign private operators. This is changing, as smaller towns and cities are growing rapidly in many developing countries. Concurrently, decentralization is shifting responsibility for services from national to smaller entities that often cannot finance and manage them effectively. Paralleling this trend, new service models in which local private firms contract with local governments or community associations to provide water supply and sanitation (WSS) services have been proposed in smaller urban contexts. The author examined how these challenges are being addressed in eight World Bank projects in Cambodia, Colombia, Paraguay, the Philippines, and Uganda. In all five countries, the government has sought public-private partnerships to promote sustainability, increase access to services (particularly for the poor), and, except in Cambodia, strengthen the role of local government. All five countries have policies that encourage greater access to services by the poor, to the extent consistent with the paramount goal of financial viability. Investment subsidies, particularly those targeting the poor, have played an important role in all cases.